Nursing in the Emergency Department During The Covid-19 Pandemic: A Qualitative Study - Yurdanur Dikmen; Özge Öner; Şenay Şener; Durdane Yılmaz Güven (Genel Tıp Dergisi)
Aim: This study aimed to determine the professional experiences of nurses working in the emergency department in the Covid-19 pandemic. Materials and Methods: In this study, in which qualitative research method was used, focus group interviews were conducted with 12 nurses working in the emergency department. Data were collected using a sociodemographic form and a semi-structured Focus Group Interview form. The data obtained after the interviews were analysed using content analysis. Results: Three main themes (fear, exposure, and working conditions) related to nurses' experiences working in the emergency department in the Covid-19 pandemic were determined. The nurses spoke most of all about the fear of the unknown. Conclusion: This study demonstrated the importance of supporting emergency nurses' crisis management, psychosocial and professional needs working during a pandemic. It is thought that any improvement work to be carried out for healthcare workers during the pandemic process will directly affect all gains during the pandemic positively.